Tools for the storage and analysis of spatial Big Data - Lisowski, Przemysław; Piórkowski, Adam; Leśniak, Andrzej (International Conference “Environmental Engineering”, 2017)
Storing large amounts of spatial data in GIS systems is problematic. This problem is growing due to ever-increasing data production from a variety of data sources. The phenomenon of collecting huge amounts of data is called Big Data. Existing solutions are capable of processing and storing large volumes of spatial data. These solutions also show new approaches to data processing. Conventional techniques work with ordinary data but are not suitable for large datasets. Their efficient action is possible only when connected to distributed file systems and algorithms able to reduce tasks. This re view focuses on the characteristics of large spatial data and discusses opportunities offered by spatial big data systems. The work also draws attention to the problems of indexing and access to data, and proposed solutions in this area.